AUTONOMOUS NERVOUS SYSTEM IMBALANCE AND LEFT VENTRICULAR STRUCTURE AND GEOMETRY IN HEALTHY INDIVIDUALS - E. M. Khurs; M. G. Evsina; A. V. Poddybnaya; P. V. Andreev; O. G. Smolenskaya (Российский кардиологический журнал, 2011)
The study was aimed at assessing the effects of autonomous nervous system (ANS) imbalance on heart structure and function in healthy individuals. In total, 50 healthy people (11 men, 39 women; mean age 35,4±10,2 years), free from cardiovascular disease or extra-cardiac pathology, were examined. All participants underwent 24-hour ECG monitoring and transthoracic echocardiography. Based on the index of sympatho-vagal balance (LF/HF), all subjects were divided into two groups: Group I (LF/HF<2,5; n=24) and Group II (LF/HF>2,5; n=26). Heart rate variability (HRV) analysis demonstrated a statistically significant decrease in HF, SDNN, NRVti during the night, and RMSSD in Group II. Therefore, a reduction in total HRV was mostly due to decreased parasympathetic activity. In Group II, end-diastolic volume and myocardial systolic stress (MSs; p=0,009) were significantly elevated, while the ratio of ejection fraction (EF) to MSs was decreased. Therefore, “optimal” wall tension during the left ventricular (LV) ejection phase was disturbed. These results were confirmed by moderate correlations between LF/HF and MSs (r=0,39; p=0,005) and between LF/HF and EF/MSs (r=-0,36; p=0,01). Even in healthy people, ANS imbalance could result in increased LF load and functional LF disadaptation. Therefore, ANS imbalance could be considered as one of the cardiovascular risk predictors.